Harmonization of Accountant Professional Ethics with Local Javanese Cultural Wisdom - Muhammad Aras Prabowo; Khusnul Khotimah; Lusiana Putri Ahmadi (Innovation Business Management and Accounting Journal, 2025)
This research aims to explore and understand how the values of local Javanese cultural wisdom can be harmonized with the ethics of the accounting profession. Accountant professional ethics are usually based on international standards, but this time the author tries to relate them to local Javanese cultural wisdom. Through various literature studi and understanding the attitudes of Javanese society, this journal can be completed. The research results show that Javanese cultural values play a role in shaping the ethical behavior of accountants. Integrating of these values with international accounting ethical standrads can improve integrity and professional performance in the local context. It is hoped that this journal will be able to help create more ethical and contextual accounting practices in Indonesia.